Framing Analysis of the Kompas' COVID-19 Coverage: January 2020 Edition - I Gusti Lanang Agung Kharisma Wibhisono (Jurnal Aspikom, 2020)
The advent of health risk situation brings about several challenges to be addressed, e.g., risk preparedness and clear information to reduce uncertainties. At the end of 2019, the world was once again confronted with a health-threatening situation: the emergence of the novel coronavirus. Media can construct health risk information through narratives or stories they provide. Nevertheless, not every pandemic represented was equal. The media could build risk perception about global or local outbreaks. In light of that, this article aims to describe how the media in Indonesia framed the novel coronavirus disease issue (COVID-19) before the pandemic. This article utilized the framing analysis method, literature review, and was guided by health and risk communication framework. This article provided contextual novelty by presenting the analysis of Indonesian newspaper coverage concerning health and risk communication. The research suggested that media play an important role in shaping public perception about health and risk by employing four frame functions: problem definition, causal interpretation, moral evaluation, and treatment recommendation.